Show that the electric potential a distance z above the centre of a horizontal circular loop of radius R, which carries a uniform charge density per unit length λ…..

Spread the love

Problem:

Show that the electric potential a distance z above the centre of a horizontal circular loop of radius R, which carries a uniform charge density per unit length λ, is given by

    \[V=\dfrac{\lambda R}{2\epsilon_0}\dfrac{1}{(z^2 + R^2)^{1/2}}\]

Obtain an expression for the electrostatic field strength as a function of z.

Explanation:

The electric potential at P(0, 0, z) is derived using the principle of superposition, summing contributions from all infinitesimal elements of the charged circular loop. The electrostatic field strength E is then obtained as the negative gradient of the potential V along the z-axis.

For a uniform charge distribution on a circular loop:

  1. Compute ( V ) using the distance formula r = \sqrt{z^2 + R^2}.
  2. Differentiate V with respect to z to get E_z.

Solution:

  1. Electric Potential V:
    The total charge on the loop is Q = 2\pi R \lambda.
    At a distance z above the center of the loop, the electric potential is given by:

        \[V = \frac{1}{4\pi \epsilon_0} \int \frac{\lambda \, dl}{r}\]


    For a uniform loop, dl = R \, d\theta, and r = \sqrt{z^2 + R^2} (constant for all points on the loop).

Substituting:

    \[V = \frac{\lambda}{4\pi \epsilon_0} \int_0^{2\pi} \frac{R \, d\theta}{\sqrt{z^2 + R^2}}\]

The integral simplifies as \sqrt{z^2 + R^2} is constant:

    \[V = \frac{\lambda R}{4\pi \epsilon_0 \sqrt{z^2 + R^2}} \int_0^{2\pi} d\theta\]


    \[V = \frac{\lambda R}{4\pi \epsilon_0 \sqrt{z^2 + R^2}} (2\pi)\]


    \[V = \frac{\lambda R}{2 \epsilon_0 \sqrt{z^2 + R^2}}\]

This matches the given expression for V.

  1. Electric Field E_z:
    The field strength along the z-axis is obtained from the derivative of V:

        \[E_z = -\frac{\partial V}{\partial z}\]

Substitute V = \frac{\lambda R}{2 \epsilon_0 \sqrt{z^2 + R^2}}:

    \[E_z = -\frac{\partial}{\partial z} \left( \frac{\lambda R}{2 \epsilon_0 \sqrt{z^2 + R^2}} \right)\]


    \[E_z = -\frac{\lambda R}{2 \epsilon_0} \cdot \frac{\partial}{\partial z} \left( (z^2 + R^2)^{-1/2} \right)\]


Using the chain rule:

    \[\frac{\partial}{\partial z} \left( (z^2 + R^2)^{-1/2} \right) = -\frac{1}{2} (z^2 + R^2)^{-3/2} \cdot 2z = -\frac{z}{(z^2 + R^2)^{3/2}}\]

Substitute back:

    \[E_z = -\frac{\lambda R}{2 \epsilon_0} \cdot \left( -\frac{z}{(z^2 + R^2)^{3/2}} \right)\]


    \[E_z = \frac{\lambda R z}{2 \epsilon_0 (z^2 + R^2)^{3/2}}\]


Final Answer:

The electric potential is:

    \[V = \frac{\lambda R}{2 \epsilon_0 \sqrt{z^2 + R^2}}\]


The electric field strength along the ( z )-axis is:

    \[E_z = \frac{\lambda R z}{2 \epsilon_0 (z^2 + R^2)^{3/2}}\]

Leave a Comment

Your email address will not be published. Required fields are marked *

Scroll to Top